Digital health citizens and the future of the NHS - Powell, J; Newhouse, N; Boylan, A; Williams, V (SAGE Publications, 2016)
Health systems worldwide are facing unprecedented challenges as they seek to deliver better value healthcare against a backdrop of increasing levels of chronic disease, ageing populations, global financial crises and reduced public spending, and digital health tools and services are widely touted as being part of the answer, offering low-cost and patient-centred solutions.